2006
DOI: 10.1111/j.1525-142x.2006.00113.x
|View full text |Cite
|
Sign up to set email alerts
|

Is retinoic acid genetic machinery a chordate innovation?

Abstract: Development of many chordate features depends on retinoic acid (RA). Because the action of RA during development seems to be restricted to chordates, it had been previously proposed that the "invention" of RA genetic machinery, including RA-binding nuclear hormone receptors (Rars), and the RA-synthesizing and RA-degrading enzymes Aldh1a (Raldh) and Cyp26, respectively, was an important step for the origin of developmental mechanisms leading to the chordate body plan. We tested this hypothesis by conducting an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
76
1
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(84 citation statements)
references
References 50 publications
4
76
1
3
Order By: Relevance
“…One interesting feature of this analysis is the confirmation of the absence of most components of the RA machinery in appendicularian tunicates (Cañestro et al, 2006). Thus, O. dioica is an exception within chordates, because it lacks most elements of the RA signaling cascade (rar, aldh1, and cyp26) and because it does not seem to use the same pathway in AP patterning during embryonic development .…”
Section: Evolutionary Origins Of Ra Signalingmentioning
confidence: 83%
See 2 more Smart Citations
“…One interesting feature of this analysis is the confirmation of the absence of most components of the RA machinery in appendicularian tunicates (Cañestro et al, 2006). Thus, O. dioica is an exception within chordates, because it lacks most elements of the RA signaling cascade (rar, aldh1, and cyp26) and because it does not seem to use the same pathway in AP patterning during embryonic development .…”
Section: Evolutionary Origins Of Ra Signalingmentioning
confidence: 83%
“…amphioxus and different tunicate species) provided evidence for roles of RA during development of all chordates (Cañ-estro and Postlethwait, 2007;De Bernardi et al, 1994;Denucé, 1991;Hinman and Degnan, 1998;Holland and Holland, 1996;Katsuyama et al, 1995). Moreover, recent studies have suggested a possible presence of this pathway in other deuterostomes: bioinformatic analyses have revealed rar, cyp26, and raldh homologs in the genome of the sea urchin Strongylocentrotus purpuratus and raldh and cyp26 homologs in EST sequences from the hemichordate Saccoglossus kowalevskii (Cañestro et al, 2006;Howard-Ashby et al, 2006;Marlétaz et al, 2006;Ollikainen et al, 2006;Simões-Costa et al, 2008).…”
Section: Evolutionary Origins Of Ra Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations raise the question of how tunicates, with their altered Hox clusters, are still able to develop a chordate body plan. In chordates, and deuterostomes more generally, temporal colinearity is regulated by the Retinoic-Acid (RA) signaling pathway which controls the antero-posterior patterning of the embryo (Cañestro et al, 2006;Marlétaz et al, 2006). However, axial patterning in tunicates seems to have become independent of RA-signaling, with the genes of the RA machinery even being lost in Oikopleura .…”
Section: Implications For Chordate Evo-devomentioning
confidence: 99%
“…A significant role for RA signaling in the development of endoderm might appear somewhat surprising because endoderm is a germ layer of all multi-layered embryos, whereas the RA signaling system has often been described as a signaling system that has arisen during chordate evolution [3,4]. There is now, however, evidence that homologues of enzymes and receptors necessary for RA signaling exist in different invertebrates [5][6][7], but it is still not clear as to whether or not these homologues function in an analogous manner. If in fact they have alternate functions, then retinoic acid signaling may be an adaption that occurred during evolution and unique to the chordates.…”
Section: Introductionmentioning
confidence: 99%